Exploring the potential reservoirs of Pseudomonas spp. bacteria at meat processing factories and poultry farms - D. S. Bataeva; Yu. K. Yushina; A. A. Semenova; E. V. Zaiko; M. A. Grudistova (Теория и практика переработки мяса, 2025)
One of the microorganisms that cause spoilage of meat during its storage is the bacteria Pseudomonas. To prevent contamination of the finished products with these bacteria, it is important to find the places at the enterprise where they aggregate. Within the framework of this study, the objects and premises of the production facilities at meat processing factories and poultry farms were explored to detect their contamination with bacteria of Pseudomonas spp. The potential reservoirs of those bacteria were defined at these plants. In addition, the species diversity of Pseudomonas was established at the production facilities environment at the enterprises. 27 production facilities environments (structures, equipment, package containers) were examined for the presence of bacteria with the method of washings. The samples were examined to detect Pseudomonas bacteria, with their subsequent identification with the method of time-of-flight mass spectrometry MALDI-Tof-MS. 487 strains of bacteria of the genus Pseudomonas were isolated, which strains are represented by 47 species. As a result of the study it was found that all 27 production facilities were contaminated with various species of Pseudomonas. From two to fourteen species of Pseudomonas bacteria were detected at all facilities. 12 facilities of the enterprise for slaughter and processing of broiler chickens were contaminated with Pseudomonas gessardii. Pseudomonas bacteria spp. (identification is traced down only to its genus) were found at 10 objects. Pseudomonas tolaasii and Pseudomonas brenneri were found at 9 and 8 objects, respectively. The surfaces of 6 objects demonstrated contamination with Pseudomonas chlororaphis ssp chlororaphis and Pseudomonas koreensis. Other Pseudomonas species were found at 1–5 sites. Pseudomonas fluorescens were detected at 8 pork processing plant sites, Pseudomonas gessardii were found at 5 sites. 4 sites were contaminated with Pseudomonas chlororaphis ssp. chlororaphis and Pseudomonas koreensis, 3 objects contained Pseudomonas tolaasii, Pseudomonas spp., Pseudomonas rhodesiae, Pseudomonas libanensis and Pseudomonas extremorientalis. The remaining species of Pseudomonas were found at one or two sites in the territory of the pork processing plant. It was found that all production environment sites, regardless of their distance from the raw materials and the finished products, were contaminated with Pseudomonas bacteria. At the same time, the sites that had no contact with the food products showed wider diversity of Pseudomonas species than in the places where the contact took place. Thus, all the explored objects of the production environment at the pork processing enterprises and the facilities for slaughter and processing of broiler chickens are the potential reservoirs of Pseudomonas bacteria.